2013
DOI: 10.1080/19443994.2013.769668
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial-aerosol emission from wastewater treatment plant

Abstract: A B S T R A C TBioaerosols' emission from an activated sludge wastewater treatment plant with surface aerators was surveyed from November 2009 to July 2010. Health effects among plant workers were assessed by checklist and through interviews by an internist. Samples were collected by the Anderson sampler in eight days of the year and analyzed for Standard Plate Count, Total Coliforms, Fecal Coliforms, and Fecal Streptococci. It was found that most sewage treatment plant's staffs were adversely affected as a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…Bioaerosols emitted from different stages in an activated sludge wastewater treatment plant have been collected by an Anderson sampler (Malakootian et al 2013). The maximum concentrations of bacterial aerosols have been found in the sludge aerobic digester unit (1537 CFU/m 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bioaerosols emitted from different stages in an activated sludge wastewater treatment plant have been collected by an Anderson sampler (Malakootian et al 2013). The maximum concentrations of bacterial aerosols have been found in the sludge aerobic digester unit (1537 CFU/m 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Around 10% of hospital infections in hospitalized patients without any underlying disease were caused by organisms transmitted through air (15). Moreover, the degree of emission of bioaerosols in the air surrounding Kerman city wastewater treatment plant was examined by Malakootian et al (16). As hospital infection caused problems such as prolongation of hospitalization time, development of disease, decreased productivity in a working environment as well as staff absence; such problems placed a heavy cost burden to health systems in developing countries (17).…”
Section: Introductionmentioning
confidence: 99%
“…Bioaerosol concentrations are usually higher during night than day time with a lack of solar radiation and lower temperatures to reduce bioaerosols (Karra and Katsivela, 2007). Furthermore, bioaerosols may have higher concentrations in colder (winter and fall) months than warmer (spring and summer) months because of temperature differences (Malakootian et al, 2013). However, Fracchia et al 2006 found no seasonal trends in bioaerosol concentrations in their study in Italy.…”
Section: Environmental Factorsmentioning
confidence: 89%
“…Bioaerosol concentrations from activated sludge systems are dependent on a number of operational and environmental parameters. When inhaled from the air or ingested after touching a surface contaminated with pathogenic bioaerosols, they can cause negative health consequences to sewage treatment workers such as stomach pain, fatigue, dizziness, eye irritation and headaches (Oppliger et al, 2005;Malakootian et al, 2013). Neighboring communities could also be at risk if concentrations are high enough and they are in close proximity to activated sludge treatment plants.…”
Section: Summary Of Data On Pathogens In Activated Sludge Systems (Bimentioning
confidence: 99%
See 1 more Smart Citation